2012
DOI: 10.1038/pr.2011.39
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence for an impulsivity-based thrifty eating phenotype

Abstract: IntroductIon: Low birth weight is associated with obesity and an increased risk for metabolic/cardiovascular diseases in later life. results: The results of the snack delay test, which encompassed four distinct trials, indicated that the gender × intrauterine growth restriction (IUGR) × trial interaction was a predictor of the ability to delay the food reward (P = 0.002). among children with normal birth weights, girls showed a greater ability to delay food rewards than did boys (P = 0.014).In contrast, among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
56
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 53 publications
10
56
2
2
Order By: Relevance
“…Similar to previous research, PT-adults had less liking for protein foods (Barbieri et al, 2009; Migraine et al, 2013) and wine (Cooke, 2004; Roberts et al, 2013), and greater liking for sweets (Ayres et al, 2012; Barbieri et al, 2009; Silveira et al, 2012) than FT-adults. The PT-adults with lower birth weight also had greater liking for sweets while less liking for fruits/vegetables, consistent with prior findings (Barbieri et al, 2009; Kaseva et al, 2013; Silveira et al, 2012). Contrary to previous findings (Stein et al, 2006), birth weight was not associated with liking for salty foods, which could be explained by differences in the study samples, as we only included preterm adults with birth weight <1850 grams.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to previous research, PT-adults had less liking for protein foods (Barbieri et al, 2009; Migraine et al, 2013) and wine (Cooke, 2004; Roberts et al, 2013), and greater liking for sweets (Ayres et al, 2012; Barbieri et al, 2009; Silveira et al, 2012) than FT-adults. The PT-adults with lower birth weight also had greater liking for sweets while less liking for fruits/vegetables, consistent with prior findings (Barbieri et al, 2009; Kaseva et al, 2013; Silveira et al, 2012). Contrary to previous findings (Stein et al, 2006), birth weight was not associated with liking for salty foods, which could be explained by differences in the study samples, as we only included preterm adults with birth weight <1850 grams.…”
Section: Discussionsupporting
confidence: 84%
“…Individuals born prematurely also may not appropriately self-control these less healthy food preferences. We found that PT-adults had less dietary restraint than the FT-adults or norms of college-aged students, which may parallel findings of higher impulsive eating behaviors among preschoolers born with intrauterine growth restriction (Silveira et al, 2012). …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Interestingly, the quality of mother-infant interaction is also an important factor persistently modulating the HPA axis functioning (Francis, Diorio, Liu, & Meaney, 1999;Liu et al, 1997;McGowan et al, 2009); this could affect eating in response to emotional stimuli and ultimately growth in IUGR girls, as seen in our study. The associations described here were limited to IUGR girls, and not boys, similarly to what we have previously described (Barbieri et al, 2009;Silveira et al, 2012). Other studies have also shown sex differences in the moderator effect of genetic polymorphisms (e.g.…”
Section: Discussionsupporting
confidence: 70%
“…Mothers of SGA infants also have higher frequency of behaviors indicative of feeding difficulties than their appropriate for gestational age counterparts (Mullen, Coll, Vohr, Muriel, & Oh, 1988). Therefore IUGR children may suffer from a double burden of vulnerability in terms of feeding modulation: their metabolic adaptations lead to persistent programming of appetite, food preferences (Ayres et al, 2012;Barbieri et al, 2009;Crume et al, 2013;Kaseva et al, 2013;Lussana et al, 2008;Migraine et al, 2013;Perala et al, 2012;Silveira et al, 2012;Stein et al, 2009) and chronic adult disease risk (Barker et al, 1989;Bettiol et al, 2007;Hales et al, 1991;Ravelli et al, 1976); in addition, their motherinfant relationship may affect feeding behaviors and long-term overweight risk. Interventions aiming at improving this interaction may be of benefit, especially for this population of IUGR children.…”
Section: Discussionmentioning
confidence: 95%